Morphological and Molecular Systematics of Bulbophyllum Thou, in Peninsular Malaysia - Hosseini, Shahla (2011)
The largest member of the subtribe Bulbophyllinae (Orchidaceae) has been defined as Bulbophyllum, a genus which forms a large, pantropical, and poorly studied group of orchids in Peninsular Malaysia. Based on this study, members of this large genus have undergone extreme reduction in number of species in the natural habitat and have acquired efficient adaptation to the canopy environment. In this study 57 Bulbophyllum taxa were collected and 48 species were identified to species level, whereas the other 9 species were not identified due to lack of flowering structure but they are separate individual species as confirmed by DNA sequences. The most widely accepted classification system is based exclusively on floral morphology, and no significant molecular studies of Bulbophyllum in Peninsular Malaysia have been done. To study the systematics of this genus, structural characters were used together with molecular evidence to generate molecular systematic hypotheses by using PAUP* 4.0 b 10 and Mr Bayes 3.1.1. The structural portion of this study was performed using both qualitative and quantitative characters of rhizome, pseudobulb, leaf and flower. Phenetic and cladistic analyses were conducted for morphological data of 38 different species and molecular cladistic analyses has been carried out for the 57 taxa with parsimony, likelihood and Bayesian methods. Four nucleotide sequence data sets from two distinct genomes cpDNA genes (rbcL, matK, trnL-F) and nuclear gene (ITS) were used to construct independent cladograms of the Bulbophyllum taxa. The morphological clustering of 11 sections of Bulbophyllum with high congruency corresponded with prior descriptions, with the following exceptions: species of sections Hirtula and Cirrhopetalum divided into two separate clusters. Morphological character analysis placed B. coniferum from section Globiceps inside section Aphanobulbon, and B. mutabile from section Aphanobulbon inside section Desmosanthes. Based on the quantitative results B. medusae was placed inside section Cirrhopetalum but qualitative characters have supported the status of this species inside section Desmosanthes which corresponded with the earlier classification. Cladistic analysis was highly congruent with phenetic result however grouping of the sections was much more corresponded with molecular data. Separate parsimony analysis as well as combined Bayesian analysis of four gene regions except for rbcL, supported a monophyletic status (BP100, PP100) for 12 out of 13 sections of Peninsular Malaysian Bulbophyllum. The molecular results gave strong evidence (BP90-100, PP100) that the generic status of section Cirrhopetalum could no longer be supported, as it was deeply embedded within the genus Bulbophyllum. This section was a sister group to section Desmosanthes in all the different analyses, so it cannot be considered as a separate genus. Section Hirtula was the only section with a paraphyletic status. It was divided into B.dayanum which is a sister to section Careyana; B. hirtulum and B. limbatum are sister group to section Aphanobulbon. The combined molecular data analysis confirmed the status of B. medusae as a species of section Cirrhopetalum. Significantly, the status of some species through clustering analysis obtained from structural characters was in congruence with the molecular analysis and the species grouping of sections Sestochilus, Epicrianthes, Monilibulbus and Careyana was similar with the combined molecular data analysis. In this study, molecular systematics analysis had provided a robust estimation for the phylogenetic relationships of Bulbophyllum which suggested that the Internal Transcribed Spacer (ITS) and cpDNA markers (matK and trnL-F) with the exception of rbcL (with low level of resolution among species) are reliable markers for the phylogenetic studies of Bulbophyllum within the studied sections in Peninsular Malaysia.